Analysis of Furnace Performance Efficiency 201-H-001 Prefractionation Unit PT Trans-Pacific Petrochemical Indotama Tuban-East Java - Nurkhopipah, Siti; Hapsari, Farlina; Asminah, Ninin (Gema Wiralodra, 2024)
Petroleum processing generally begins with a heating process, so equipment is needed to heat the crude oil before entering the fractionation column. This heating is closely related to the separation of fractions based on differences in boiling points. Heating at a fairly high temperature is used by a furnace, where the heat source comes from gas fuel. Based on the discussion above, furnace efficiency is fascinating to calculate as an indication of whether or not the furnace is operational. This efficiency calculation is also a reference for PT. Trans-Pacific Petrochemical Indotama to shut down and repair equipment, especially furnaces. This research aims to understand the furnace's working principles, determine the parameters that influence furnace performance, and calculate the efficiency of Furnace 201-H-001 in the Prefractionation unit. The results obtained in this research are that there are variables used to calculate thermal furnace efficiency. These variables are air temperature, fuel gas temperature, fuel gas flow, flue gas temperature, theoretical air requirements, and excess air in terms of efficiency and combustion reactions. The results of the furnace efficiency calculations were 78.03%, 77.34%, and 77.75% respectively. The minimum thermal efficiency value ranges from 75 - 80%, so it can be said that the furnace in this research is still suitable for use.